TT3, a More Practical Indicator for Evaluating the Relationship Between Sarcopenia and Thyroid Hormone in the Euthyroid Elderly Compared with FT3 [Letter] - Sun J; Huang J; Lu W (Clinical Interventions in Aging, 2023)
Jingxia Sun, Jianhao Huang, Wensheng Lu Department of Endocrinology and Metabolism, Guangxi Academy of Medical Sciences and the People’s Hospital of Guangxi Zhuang Autonomous Region, Nanning, Guangxi, 530021, People’s Republic of ChinaCorrespondence: Wensheng Lu, Email Lwswxqz@163.com